ANALYSIS OF THE EFFECTIVENESS OF IMPLEMENTING THE FOUR EYES PRINCIPLE TO CONTROL NPF IN ISLAMIC BANKS: LITERATURE REVIEW - Edi Faisal Harahap (CV. RADJA PUBLIKA, 2025)
This study discusses the issue of Non-Performing Financing (NPF) which is a major challenge for Islamic banks in Indonesia, with the aim of exploring the effectiveness of implementing the Four Eyes principle in controlling financing risk. The scope of the research includes analysis of internal policies and decision-making practices that affect the financial performance of Islamic banks. The method used is a literature review approach, with data collection from academic databases such as Scopus and Google Scholar. Data are analyzed using thematic analysis to provide insight into current issues related to risk management. The results of the study indicate that the implementation of the Four Eyes Principle can significantly reduce the NPF ratio, with success influenced by organizational culture and staff training. These findings indicate that collaboration in decision-making is a key factor in mitigating financing risk. The implication of these results is the need for strengthening policies and ongoing training to improve the effectiveness of risk management in Islamic banks.